Age Determination Technique According to the Calcium Accumulation in Bony Structures of Capoeta umbla (Heckel, 1843) - Calta, Metin; Sen, Dursun; Aydin, Rahmi; Koprucu, Kenan; Canpolat, Ozgur; Coban, Mehmet Zulfu (Medwell Online, 2010)
In this study, the ages of individuals belonging to Capoeta umbla (Heckel, 1843) populations obtained from Keban Dam lake and Hazar lake were determined from 5 different bony structures and the level of calcium mineral of each bony structure was measured by atomic absorption spectrophotometer The results were compared between populations of Keban Dam lake and Hazar lake In addition, the determined calcium element was statistically examined according to age, length and weight of fishes The relationships between accumulation of calcium in some bony structures and fish size (both length and weight) and age were found insignificant (p>0 05) However, the best relationships between calcium accumulation and fish size and age were found in vertebra, otolith and dorsal fin ray In conclusion, although there were some differences of calcium accumulation in the same bony structures of fishes obtained from Keban Dam lake and Hazar lake in general there were similarities In addition, the accumulation of calcium on some bony structures was observed to increase with the increasing of age, length and weight of fishes but these Increases were not statistically important
Keywords: Capoeta umbla; calcium; age determination; Keban Dam lake; Hazar lake; vertebra